IMPROVING PRODUCTIVITY THROUGH THE DESIGN OF A QUALITY MANAGEMENT SYSTEM BASED ON THE ISO 22000:2018 STANDARD - CONTRERAS-RIVERA, ROBERT (2024)
THE OBJECTIVE OF THIS RESEARCH IS TO DEMONSTRATE, THROUGH THE DESIGN OF A QUALITY MANAGEMENT SYSTEM BASED ON THE ISO 22000:2018 STANDARD, THE INCREASE IN THE PRODUCTIVITY OF THE MOLINERA COMPANY.THIS IS BECAUSE, IN THIS ORGANIZATION, WHOSE FUNCTION IS THE PRODUCTION OF FLOUR, PASTA AND COOKIES DERIVED FROM WHEAT; LOW PRODUCTIVITY HAS BEEN EVIDENT DUE TO THE ABSENCE OF STANDARDIZATION IN ITS PROCESSES AND INSUFFICIENT SYSTEMATIZATION IN FOOD SAFETY MANAGEMENT.THEREFORE, QUANTITATIVE AND NON-EXPERIMENTAL METHODOLOGY HAS BEEN USED, THROUGH THE USE OF DESCRIPTIVE STATISTICS FOR THE INTERPRETATION OF DATA.THIS IS HOW, WHEN CARRYING OUT A BASELINE DIAGNOSIS, WHEN USING THE STATISTICAL SOFTWARE IBM SPSS STATICS, ANALYZING THE INITIAL PRODUCTIVITY AND COMPARING IT WITH THAT OBTAINED AFTER THE PREDICTION OF ESTIMATION VALUES OF THE DESIGN OF THE QUALITY MANAGEMENT SYSTEM FOR THE INTERVAL OF TWELVE MONTHS, AN INCREASE OF 33.4% IN PRODUCTIVITY WAS OBTAINED.LIKEWISE, REGARDING THE EFFICIENCY AND EFFECTIVENESS INDICATORS, WHICH IMPROVED SIGNIFICANTLY.CONVERTING THIS DESIGN INTO AN OPTIMAL ALTERNATIVE FOR IMPROVEMENT IN ORGANIZATIONS. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.